EDUKASI KESEHATAN MENTAL REMAJA MELALUI DETEKSI DINI STRES DAN KECEMASAN BERBASIS KOMUNITAS LOKAL - Dhiya Urrahman; Pritta Yunitasari; Laily Mualifah; Murti Krismiyati; Benny Karuniawati (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2025)
Adolescents face academic and social pressures that can trigger stress and anxiety, requiring educational interventions to improve coping skills. This community service activity aimed to provide mental health education to adolescents in Dusun Manukan, Kalurahan Sendangsari, Kapanewon Pajangan, Bantul Regency, and enhance their understanding of early detection strategies for stress and anxiety. Methods included interactive education, group discussions, and Q&A sessions, involving 34 active adolescents. Activity stages included material preparation and coordination, educational implementation, and evaluation through Q&A and participant observation. Results indicated increased understanding of stress, anxiety, and coping strategies, especially in recognizing early stress signs and managing emotional responses adaptively. This initiative highlights the importance of empowering adolescents as mental health agents in the community while strengthening preparedness and social skills. Continuous training is recommended to maintain acquired knowledge and skills.